RESERVA GEOBOTÁNICA DEL PULULAHUA, FORMACIONES VEGETALES, DIVERSIDAD, ENDEMISMO Y VEGETACIÓN - Cerón, Carlos (2004)
The Pululahua Geobotamcal Reserve is located in Calacalí. Quito, province of Pichincha, with coordinates 78*26'-78'32’W and 00*03’- 00‘ 08'N. and with an extension of 3.300 Has It comprises the following life zones: low montane humid forest, low montane dry forest and premontane humid forest Fieidworti was carried on from 1987 unbl now. and all the trails were visited. Random colections were made in 15 localities, and fotowmg the transects methodology. The treneects located in scrubby vegetation with shrubs of j» 50 m high, and with no defined DBH were of 50 x 2 m (0.01 Ha), and transects located in the forested areas with trees with ¿2.5 m high were of 50 x 2 m x 10 (0.1 Ha). The botaneal identifications made at the Alfredo Paredes (QAP) and National Herbaria (QCNE). and the vouchers were also deposited in these two institutions 2 Cerón: Flora del Pululahua There were e vegetation formations: Lower Montane Ever-green Gallery Forest; Montane Cloud Forest; Rocky Semi-dry Montane Scrub; Semi-dry Montane Scrub; Humid Montane Scrub; "Ceja Andina' or Ever-green High-montane Forest; Cultivated lands; and Eqwsetum lands. There was an alpha diversity between 28-46 species of 1 2.5 cm OBH in the various localities with 0.1 Has. and between 16-51 species of i 50 cm high on the 0,01 Has. From the 905 species and 137 families. 92 are endemic (10.2 %). 815 are native and 91 cultivated. nearly half has vernacular names, and 261 are useful. Phytogenetically there are 8 licopodttphyta. 3 Equisetophyta, 76 Potypodtophyta. 4 Pmophyta. and 814 Magnokophyta (564 Magnokopsidee and 250 Liliopsidae). According to the habit, there are 9: herbs. 379 •peoes; shrubs. 158; epiphytes. 130; trees. 121; cumbers, 56; sub-shrubs, 31; hemiep*)hytee. 16. kanas, 8; and parasitic. 7. The most numerous famikes are: Orchidaceae. 105 tpeoee. Asteraceae. 70; Poaceae. 45; Soianeceee. 36. Bromekaceae. 32; Fabaceae and Piperaceee. 29: and the rest of families wNh less than 25 species